2021
DOI: 10.1111/jcmm.16776
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic studies of CD19 CAR T cell in human leukaemic xenograft models with dual‐modality imaging

Abstract: In recent years, chimeric antigen receptor T (CAR T)‐cell therapy has shown great potential in treating haematologic disease, but no breakthrough has been achieved in solid tumours. In order to clarify the antitumour mechanism of CAR T cell in solid tumours, the pharmacokinetic (PK) and pharmacodynamic (PD) investigations of CD19 CAR T cell were performed in human leukaemic xenograft mouse models. For PK investigation, we radiolabelled CD19 CAR T cell with 89Zr and used PET imaging in the CD19‐positive and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These data could be the cause of cell inactivation before targeting tumors, a low tumor accumulation of CAR T cells, and no tumor regression [232]. Wu et al labeled CD19 CAR T with 89 Zr-oxine to study the pharmacokinetic and pharmacodynamic in human leukemic xenograft mouse models [233]. Their results were quite like those previously reported, CAR T cells were successfully labeled without affecting their viability and proliferation and showed high 89 Zr retention (>80%).…”
Section: Labeling Of Genetic Engineering Cellsmentioning
confidence: 59%
“…These data could be the cause of cell inactivation before targeting tumors, a low tumor accumulation of CAR T cells, and no tumor regression [232]. Wu et al labeled CD19 CAR T with 89 Zr-oxine to study the pharmacokinetic and pharmacodynamic in human leukemic xenograft mouse models [233]. Their results were quite like those previously reported, CAR T cells were successfully labeled without affecting their viability and proliferation and showed high 89 Zr retention (>80%).…”
Section: Labeling Of Genetic Engineering Cellsmentioning
confidence: 59%
“…Considering CAR T cells as the “live” drug, their survival and proliferation in vivo are prerequisites for realizing the therapeutic effects. [ 35 ] However, methods for labeling CAR T cells can neither tell the difference between live and dead cells nor track the proliferated CAR T cells. Consequently, strategies aiming at imaging the viability of CAR T cells are also essential.…”
Section: Imaging the Viability Of Car T Cellsmentioning
confidence: 99%
“…Later, Wu and Wang et al applied 89 Zr-oxine to study the pharmacokinetics (PK) and the pharmacodynamics (PD) of CD19 CAR T cells in human leukemic xenograft mouse models. [35] Their PK and PD results suggested that 89 Zr-oxine can be used for the validation of the targeting ability of CAR and is likely to be used for screening targets and predicting the efficacy of CAR T cells. However, this strategy has some limitations: 1) direct labeling of the radiotracer into cells cannot reveal information other than the biodistribution of injected parental cells in vivo; 2) they did not validate their finding in a Raji xenograft model.…”
Section: Zirconium-oxinementioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 However, there are obstacles in the ADME and PK evaluation of adoptively transferred cells. For genetically modified cells, PK studies are performed using flow cytometry and quantitative polymerase chain reaction (qPCR) techniques, 10 , 11 , 12 while for other cells, such methods may not be available. The human‐specific hAlu gene can be used to determine the PK of Mesenchymal stem/stromal cells (MSCs) by qPCR analysis, but only murine xenograft models.…”
Section: Introductionmentioning
confidence: 99%